INTEROPERABILITY AND STANDARDISATION IN THE DEPARTMENT OF DEFENCE: AN EXPLORATORY STUDY - J. De Waal; A.J. Buys (South African Journal of Industrial Engineering, 2012)
ENGLISH ABSTRACT: The political changes in South Africa have extended its international obligations by actively involving it in the social wellbeing of troubled African states. Under the auspices of the United Nations, this role is manifested in peacekeeping operations and other standard international practices. The ability of African allied forces to train, exercise, and operate efficiently, effectively, and economically together depends on the interoperability of their operational procedures, doctrine, administration, materiel and technology. This implies that all parties must have the same interpretation of ‘interoperability’. In this study, a conceptual model that explains interoperability and standardisation in terms of a systems hierarchy and the systems engineering process is developed. The study also explores the level of understanding of interoperability in the South African Department of Defence in terms of the levels of standardisation and its relationship to the concepts of systems, systems hierarchy, and systems engineering. AFRIKAANSE OPSOMMING: Die politieke veranderinge in Suid-Afrika het daartoe aanleiding gegee dat verdere internasionale verpligtinge die land opgelê is. Suid-Afrika, in samewerking met mede-Afrika lande en onder toesig van die Verenigde Nasies, moet deur middel van vredesoperasies by onstabiele Afrika lande betrokke raak. Die vermoë om gesamentlik aan vredesopleiding, vredesoefeninge en vredesoperasies op ‘n effektiewe, doeltreffende en ekonomiese wyse deel te neem, vereis dat daar versoenbaarheid tussen onderlinge operasionele prosedures, doktrine, administrasie, materieel en tegnologie is. Dit beteken dat alle partye eens omtrent die begrip ‘versoenbaarheid’ moet wees. In hierdie studie is ‘n konseptuele model wat versoenbaarheid en standaardisasie verduidelik in terme van die stelselhiërargie en die stelselingenieursweseproses ontwikkel. Hierdie studie het ook die vlak van begrip en verstaan van versoenbaarheid in die Suid-Afrikaanse Departement van Verdediging in terme van die vlakke van standaardisasie en die verhouding tot die konsepte van stelsels, stelselhiërargie en stelselingenieurswese ondersoek.